PENGARUH COVID-19 TERHADAP KONDISI SOSIAL BUDAYA DI KOTA MALANG DAN KONSEP STRATEGIS DALAM PENANGANANNYA - Yanuarita, Heylen Amildha; Haryati, Sri (Jurnal Ilmiah Widya Sosiopolitika; Vol 2 No 2 (2020): ISU PARIWISATA DAN KESEHATAN DALAM PERSPEKTIF SOSIAL DAN POLITIK, 2021)
This study aims to analyze how the spread of the corona virus in Malang City and how it affects socio-cultural conditions and find out strategic steps in handling efforts. The research method used is descriptive quantitative study method assisted by a simple literature study review in accordance with the material or research discussion. The population of this research is all people of Malang City with the determination of the sample using purposive sampling technique to the local government of Malang City, those who are in charge of the health sector in Malang City, and the surrounding community in Malang City. Based on the results of the study, it was found that the spread of COVID-19 in Malang City continued to increase and had a negative socio-cultural impact, especially after the implementation of Large-Scale Social Restrictions (PSBB). Starting from the high divorce rate, limited social interaction, to social influence on women and children. Therefore, it is necessary to implement strategic steps by using social demographics based on decreasing social mobility in Malang City.  Keywords : impact of COVID19, socio-cultural, strategy